Modular regenerators for gas-turbine installations - Шевцов, А.П.; Кузнецов, В.В. (Eastern-European Journal of Enterprise Technologies, 2010)
Perspective construction of module regenerators with smooth pipe and profile heat transfer surfaces for gas turbine plants are presented. Comparison with existing regenerators of the Ukrainian and Russian manufacture is made.